Evaluation of stair motion contributes to new insights into hip osteoarthritis‐related motion pathomechanics. Issue 2 (7th August 2015) - Meyer, Christophe A.G.; Corten, Kristoff; Fieuws, Steffen; Deschamps, Kevin; Monari, Davide; Wesseling, Mariska; Simon, Jean‐Pierre; Desloovere, Kaat
ABSTRACT: Stair motion in the presence of hip osteoarthritis (OA) has received less attention than level walking. Its more strenuous aspect may shed the light on different locomotor strategies when compared to walking. We, therefore, aimed to define stair motion features associated to hip OA and to evaluate whether these specific features would differ from level walking and better characterize the hip pathological condition. Principal component and linear discriminant analyses were, respectively, used as data reduction and classification techniques. Our study highlighted that most of stair motion features associated to hip OA were similar to the ones of walking. Stair descent presented with the lowest misclassification error rate, ranging from 12% to 19% (estimated by cross‐validation). But, features that may be considered as a mechanism to reduce demand on the hip abductors were found to be more important in the stair ascent condition. This was reflected by both, greater importance in the classification rule and variance compared with walking, that is, decreased hip internal rotation moment at mid‐stance (72.50% vs. 57.63%) and increased trunk lateroflexion toward affected side (56.43% vs. 29.37%). This study emphasized the importance of investigating stair motion in hip osteoarthritic population by highlighting specific locomotor strategies. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:187–196, 2016.